Voter Behaviour of Local Community in Indonesia - Dian Trianita Lestari; Iriyani Astuti Arief; Shinta Arjunita Saputri (Resolusi: Jurnal Sosial Politik, 2021)
The research aims to determine and analyze the voter behavior of the Ambaipua Village community in regional head elections of South Konawe in 2020. This research uses political participation and voter behavior concept to see what underlying the community in determining the choice of their regional head, whether influenced by sociological, psychological or rational aspects. The data collection techniques used were interviews, literature studies and documentation. The results showed that the voting pattern of the Ambaipua Village community could be understood from three approaches, namely sociology, psychology and rational. A sociological approach in which the majority of informants stated that the religious aspect greatly affects who the candidate will be elected, that they will choose a candidate who has the same belief/religion. Meanwhile, from the psychological approach, it was found that the informants were not influenced by the political parties carrying the regional head candidates, but the majority would choose the incumbent with the assumption that they had succeeded in developing the region in the previous period. On the other hand, the rational approach was seen from the tendency of informants to choose candidate who have good political experience. Based on the results by the writers, it can be concluded that the sociological approach especially religion is more prominent than the other two approaches. This is because religious knowledge will have a great influence on aspects of people's lives, including their political choices.